PSYCHOSOCIAL CHALLENGES OF MARITAL LIFE IN INDIA: A CHRISTIAN PERSPECTIVE - Pradeep R., Johnson (Asian Horizons, 2014)
Marriage is defined as “the legally or formally recognized union of a man and a woman as partners in a relationship.” The concept of marriage has changed currently due to changes in the social, religious and political scenario. The traditional marriages are facing lot of resistance and are breaking up not only in western societies but also in India. Many young people today are scared to marry and prefer noncommitted and meaningless relationships. Many prefer to be alone or want to experimental relationships such as co-habitation or live-in relationship. Similarly, married couples who are dissatisfied with their marriage seek out for extramarital relationships. Also of concern is homosexuality which is still stigmatized and not accepted as a normal variant in many countries. We need to look at these important issues in a developing country like India.